Effects of central and peripheral fatique on impact characteristics during running - Encarnación-Martínez, A.; García-Gallart, A.; Sanchis-Sanchis, R.; Pérez-Soriano, P. (Sensors, 2022)
Fatigue and impact can represent an injury risk factor during running. The objective of this study was to compare the impact transmission along the locomotor system between the central and peripheral fatigued states during running. Tibial and head acceleration as well as shock attenuation in the time- and frequency-domain were analyzed during 2-min of treadmill running in the pre- and post-fatigue state in eighteen male popular runners (N = 18). The impact transmission was measured before and after a 30-min central fatigue protocol on the treadmill or a peripheral fatigue protocol in the quadricep and hamstring muscles using an isokinetic dynamometer. The time-domain acceleration variables were not modified either by peripheral or central fatigue (p > 0.05). Nevertheless, central fatigue increased the maximum (p = 0.006) and total (p = 0.007) signal power magnitude in the high-frequency range in the tibia, and the attenuation variable in the low- (p = 0.048) and high-frequency area (p = 0.000), while peripheral fatigue did not cause any modifications in the frequency-domain variables (p > 0.05). Furthermore, the attenuation in the low (p = 0.000)- and high-frequency area was higher with central fatigue than peripheral fatigue (p = 0.003). The results demonstrate that central fatigue increases the severity of impact during running as well as the attenuation of low and high components.